All‐Thioamidated Homo‐α‐Peptides: Synthesis and Conformation. Issue 17 (27th March 2013) - Formaggio, Fernando; Crisma, Marco; Toniolo, Claudio; Peggion, Cristina
Abstract: Replacement of a peptide bond with its thioamide surrogate is a classical method for the generation of a peptidomimetic with altered spectroscopic, conformational, physicochemical, and biological properties. In this context, we synthesized short series of terminally protected homo‐α‐oligopeptides based on the α‐amino acids Gly, Ala, and Nle, as well as their corresponding fully thioamidated analogues. For the first time, the preparation of the latter compounds was achieved in single‐step fashion through direct thionation of their oxygenated precursors. Using X‐ray diffraction analysis and NMR spectroscopy we were also able to confirm that the thioamidated α‐amino acid residues can easily adopt either folded or fully extended conformations. Abstract : Short series of terminally protected, fully thioamidated, homo‐α‐peptides were synthesized. For the first time, their preparation was achieved in single‐step fashion through direct thionation of their oxygenated precursors. Conformation analysis confirms that the thioamidated α‐amino acid residues can easily adopt either folded or fully extended conformations.